Analysis of the Effect of GRDP, Minimum Wage, and Poverty Level on Unemployment Rate in Central Java - Lena Puspita Sari; Novi Tri Putri (Journal of Research in Social Science and Humanities, 2024)
This study aims to find out how Gross Regional Domestic Product (GRDP), minimum wage, and poverty rate affect the unemployment rate in Central Java during the period 2021-2023. Using secondary data from 35 regencies / cities. The most appropriate analysis method used is the random effect model (REM).The results show that GRDP has a significant negative effect on unemployment, on the other hand, the minimum wage shows a significant positive effect, although there are indications that the poverty rate can affect unemployment, the effect is not significant. Overall, the independent variables explain the unemployment rate by 79.7%. These findings emphasize the importance of GRDP and minimum wage policy in the effort to reduce unemployment in Central Java, providing valuable insights for policy makers in formulating more effective strategies to address unemployment problems.